2021
DOI: 10.1039/d1cc04311k
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic DNA nanostructures for bottom-up synthetic biology

Abstract: Here we review our recent efforts, and those of others, on the construction of biomimetic DNA nanostructures that imitate biological structures and functionalities, and could serve as a generalised platform for engineering artificial cellular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 195 publications
(316 reference statements)
0
22
0
Order By: Relevance
“…Here, we demonstrated that the addition of the surfactant can facilitate DNA constructs' membrane spanning. Although not suitable for in vivo applications, this will provide new perspectives for nanopore use, including DNA and protein sequencing [27,49,51,52], and will enable the modeling and fine-tuning of the designs of DNA-based components of synthetic cells, such as membrane enzymes or ion channels [1,53,54]. Our findings shed light on the DNA membrane insertion issue, particularly by showing the importance of aggregation in membrane activity and helping to more deeply understand the action of surfactants in the DNA-lipid system.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that the addition of the surfactant can facilitate DNA constructs' membrane spanning. Although not suitable for in vivo applications, this will provide new perspectives for nanopore use, including DNA and protein sequencing [27,49,51,52], and will enable the modeling and fine-tuning of the designs of DNA-based components of synthetic cells, such as membrane enzymes or ion channels [1,53,54]. Our findings shed light on the DNA membrane insertion issue, particularly by showing the importance of aggregation in membrane activity and helping to more deeply understand the action of surfactants in the DNA-lipid system.…”
Section: Discussionmentioning
confidence: 99%
“…endocytosis and exocytosis), cell division, communication, viral infection and lipid homeostasis. [1][2][3] In addition, fusion of lipid bilayers has attracted a significant interest in biomedical research, as it plays a key role in liposomal-based drug delivery, [4][5][6][7][8] cell transfection, 9,10 the creation of artificial bioreactors [11][12][13] or the development of synthetic cells capable of controlled product release, 14,15 division and growth. 16 Owing to this biological and biotechnological relevance, new strategies to rationally design lipid-membrane fusion pathways would be highly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, while with membrane-based platforms it is relatively easy to establish internal heterogeneity, for instance through nesting or sequential assembly, 24 no general platform has been proposed to program local composition in membrane-less sca↵olds. Here, we leverage the structural and dynamic programmability a↵orded by DNA nanotechnology 25,26 to construct membrane-less condensates of DNA nanostructures, which can be "patterned" thanks to a reaction-di↵usion scheme [27][28][29][30] (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…through nesting or sequential assembly, 6 no general platform has been proposed to program local composition in membrane-less scaffolds. Here, we leverage the structural and dynamic programmability afforded by DNA nanotechnology 17,18 to construct membrane-less condensates of DNA nanostructures, which can be "patterned" thanks to a reaction-diffusion scheme. [19][20][21][22] This strategy can generate up to five chemically addressable, distinct micro-environments whose features can be rationalised through numerical modelling.…”
mentioning
confidence: 99%